Amplifying Lateral Flow Assay Signals for Rapid Detection of COVID‐19 Specific Antibodies. Issue 7 (11th May 2022) - Alhabbab, Rowa Y.; Alfaleh, Mohamed A.; Alsulaiman, Reem M.; Alamri, Sawsan S.; Eyouni, Mais S.; ElAssouli, M‐Zaki; Abuzenadah, Adel M.; Hashem, Anwar M.
Abstract: Rapid lateral flow immune‐assays are point‐of‐care diagnostic tools that are easy to use, cheap, and do not need centralized infrastructure. Therefore, these devices are appealing for rapid detection of the humoral immune responses to infections, particularly severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). The novel technique introduced here uses a complex of anti‐SARS‐CoV‐2 N‐protein antibodies conjugated to gold nanoparticles that are bound to five SARS‐CoV‐2 N protein conjugated to gold nanoparticles to amplify the signals obtained from the conjugated SARS‐CoV‐2 N protein and to enhance the assay detection limit. To validate the performance of the adopted lateral flow, serum from SARS‐CoV‐2 seropositive individuals and prepandamic negative samples are tested and compared to a validated enzyme‐linked immunosorbent assay (ELISA) for the detection of SARS‐CoV‐2 N protein specific IgG and IgM antibodies. The data shows that the designed lateral flow assay has an excellent sensitivity and specificity upon detecting IgM and IgG antibodies by applying only 2 µL from the serum sample to the adopted strips. Taken together, the developed lateral flow immunoassay assay provides a rapid, specific, and highly sensitive means to detect the immune responses against SARS‐CoV‐2 with only 2 µL from the serum sample. Abstract : Lateral flow immunoassays are point‐of‐care tests that can be done within minutes to detect antigens or antibodies. Here, the conventional method to develop these assays for the detection of antibodies to SARS‐CoV‐2 is improved. This improvement enhances the assay sensitivity, specificity, and limit of detection while using a very small amount from the samples.